Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Transformations : thinking through feminism, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". -- Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Cahiers du genre: « De la contraception à l’enfantement : l’offre technologique en question » - Béland, Bibiane (Recherches féministes, 2000)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du sud; approches et analyses; brésil; corps; corps des femmes; cours; discipline; discours dominant; droits des femmes*; europe; france; maternité; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Gender and environment - Buckingham-Hatfield, Susan (Routledge introductions to environment series, 2000)
Accessible and lively, this is the first introductory level text to introduce the key issues in the rapidly growing area of gender and environment. This text provides an analysis of how gender relations affect the natural environment and of how environmental issues have a differential impact on women and men. Using case studies from the developed and developing worlds, this text covers · gendered roles in the family · community and international connections · conception · giving birth · western practices · the body and the self.
Keywords: 1900-1999; corps; environnement; famille; justice environnementale; maternité; projet charge mentale; périodes historiques; ressource en ligne; thématiques

Contre le sexage - Causse, Michèle (Modernes Balland, 2000)
De même qu'un jour a disparu l'esclavage, forme d'existence longtemps admise de nombreux humains, de même disparaîtra demain le sexage, forme également admise à l'heure actuelle de l'existence des êtres humains appelés femmes (du latin foemina, de moindre foi). Dans cet ouvrage. Michèle Causse s'altache à montrer que la condition de celles qu'on appelle "dividues" n'est pas éternelle et qu'un jour prochain elles ne se laisseront plus sexiser ni sexualiser mais seront des êtres non divisibles, dotés d'un soi à soi.La construction des genres apparaitra alors pour ce qu'elle est : une monstruosité conceptuelle émanant d'un diviseur et au bénéfice de lui seul.L'inventivité lexicale est ici mise au service de toute l'espèce sapiens afin que ne règne plus sur lerre le seul langage jusqu'ici connu et placé sous le signe du phallus, à savoir l'androlecte. L'apparition de l'alphalecte à laquelle nous assistons ici met fin à l'empire du (seul) sens et instaure les conditions d'une éthique de vie pour tous les corps partants de la planète.
Keywords: 1900-1999; approches et analyses; corps; cours; discipline; europe; france; féminisme matérialiste; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; shm4000; systèmes d'oppressions; thématiques

Mort ou fif: la face cachée du suicide chez les garçons - Dorais, Michel; Lajeunesse, Simon Louis (Des hommes et des femmes en changement, 2000)
A partir de témoignages et récits de vie, cet ouvrage met en lumière la relation entre le mépris et l'ostracisme dont sont victimes les adolescents homosexuels ou considérés comme tels et leur haut taux de suicide. Une version revue et corrigée d'un document publié par le Centre de recherche sur les services communautaires de l'Université Laval (octobre 2000).
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques

Sexing the body: Gender politics and the construction of sexuality - Fausto-Sterling, Anne (Basic Books, 2000)
Discusses the causes and determining factors of gender behavior differences and sexual identity, particularly biology and societal expectations, and argues that differences between male and female are not always distinct.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme matérialiste; genre; histoire et politique; hétérosexisme; injustices épistémiques; philosophie politique; premier cycle; production des savoirs; ressource en ligne; sciences humaines; sciences sociales; sex3383; sexe/genre; sexualité; sociologie; systèmes d'oppressions; thématiques; épistémologie

L'expérience sociale du quotidien : corps, espace, temps - Haicault, Monique (2000)
Ce livre propose une articulation originale des champs du travail, du privé, des rapports sociaux et de la famille, et constitue une avancée majeure dans le champ de la sociologie des rapports sociaux. Monique Haicault rejette la stérilité de la binarisation traditionnelle, en tenant compte, concrètement et théoriquement, des processus de différenciation sociale de sexe. Son épistémologie « cubique » analyse la triade corps-temps-espace dans le contexte du quotidien et à travers les activités professionnelles, les activités familiales de socialisation, les déplacements urbains et les relations intergénérationnelles. L’utilisation de l’image vidéo donne vie à cette expérience. L’image contribue à montrer comment par leurs comportements, leurs actions, leurs propos et le sens qu’ils donnent à leur expérience, les acteurs sociaux participent de la construction de la société et de sa reproduction dynamique. L’auteure apporte une nouvelle contribution à la socialisation sexuée et à la théorie des rapports sociaux entre sexes et intra-sexe. Elle débouche sur un questionnement qu’il sera désormais difficile de passer sous silence.
Keywords: approches et analyses; corps; discipline; famille; projet charge mentale; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail

Gendered appetites: Feminisms, Dorothy Allison, and the body - Jarvis, Christina (Women's Studies, 2000)
Keywords: amériques; arts; corps; discipline; ressource en ligne; régions géographiques; sexualité; thématiques; états-unis; études littéraires

Invisible lives the erasure of transsexual and transgendered people - Namaste, Viviane K. (University of Chicago Press, 2000)
Invisible Lives est la première étude scientifique sur les personnes transgenres – travestis, drag queens et transsexuels – et sur leur vie quotidienne. À travers une étude théorique et empirique combinée, Viviane K. Namaste soutient que les personnes transgenres ne sont pas tant produites par la médecine ou la psychiatrie qu'elles sont effacées ., ou rendu invisible, dans une variété de contextes institutionnels et culturels. Namaste commence son travail en analysant deux perspectives théoriques sur les personnes transgenres - la théorie queer et les sciences sociales - montrant comment aucune d'entre elles n'a abordé de manière adéquate les problèmes les plus pertinents pour le changement de sexe : tout, de l'emploi aux soins de santé en passant par les papiers d'identité. Namaste examine ensuite certaines des inscriptions rhétoriques et sémiotiques des figures transgenres dans la culture, y compris des études sur les premières sous-cultures punk et glam rock, pour illustrer comment l'effacement des personnes transgenres est organisé dans différents sites culturels. Invisible Lives se termine par de nouvelles recherches sur certaines des préoccupations quotidiennes des personnes transgenres, proposant des études de cas sur la violence, les soins de santé, les cliniques d'identité de genre et la loi.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discours dominant; fem1000; identités LGBTQIA2+; personnes trans*; premier cycle; queer; santé; sexualité; systèmes d'oppressions; thématiques; théories féministes; vie quotidienne; violences; études culturelles

Au sujet des corps, des techniques et des féminismes dans L'invention du naturel: les sciences et la fabrication du féminin et du masculin - Oudshoorn, Nelly (L'invention du naturel: les sciences et la fabrication du féminin et du masculin, 2000)
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; cours; discipline; essentialisme; europe; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Dorothy Allison : la peau porte-parole - Peterson, Michel (Nuit blanche, 2000)
Portrait et parcours de cette écrivaine américaine, à partir de son recueil de textes sur l'amour lesbien, intitulé «Peau».
Keywords: amériques; approches et analyses; arts; corps; discipline; lesbianisme; personnes lesbiennes; régions géographiques; thématiques; états-unis; études littéraires

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme